Production of Extracellular Polysaccharides by a Rhizobium Species from Root Nodules of Vigna mungo (Hepper) - Nirmala, Dr. P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe ability of ten Rhizobium strains, isolated from root nodules of leguminous crop, Vigna mungo (L.) Hepper were tested for their production of Extracellular Polysaccharides (EPS) in Yeast Extract Mineral (YEM) medium. Among the ten strains, maximum amount of EPS was produced by Rhizobium Vm6 strain (1680 Âµg/mL). The maximum amount of EPS production by Rhizobium strain was achieved by optimizing the cultural conditions (Carbon and Nitrogen sources). The EPS production was maximum, when the medium was supplemented with mannitol (2%) and potassium nitrate (0.2%) which was accompanied by a great increase in the production compared to the control. The EPS contained glucose, galactose, xylose, rhamnose and raffinose, which were identified by paper chromatography.